Defining post-obstructive diuresis following posterior urethral valve ablation - Lavoie, Callum; Chun, Brian; Do, Christine; Baker, Zoë; Friedlich, Philippe; Chang, Andy Y. (Frontiers in Pediatrics, 2025)
IntroductionPosterior urethral valves (PUV) are the most common cause of congenital lower urinary tract obstruction. Patients are at risk for post-obstructive diuresis (POD) following management of this obstruction which may prolong and/or complicate their subsequent hospital course. Despite this known physiologic effect, there is minimal data to define which patients are at highest risk for POD. Our objective was to define an initial urine output threshold for neonatal post-obstructive diuresis.MethodsA retrospective chart review was conducted on patients that were admitted to our Newborn and Infant Critical Care Unit (NICCU), in a tertiary care children's hospital, between 2004 and 2019 and underwent cystoscopic valve ablation for PUV. Outcomes of interest were length of hospital stay after posterior urethral valve ablation, serum creatinine and electrolyte values, fluid intake, and urine output at 4- and 24-h post-valve ablation. Chi-squared, Fisher's exact, and T-tests were conducted for descriptive statistical analyses as appropriate. Logistic regression analyses were conducted with adjusted models including patient demographic and clinical data.ResultsForty patients met inclusion criteria and the mean age at time of valve ablation was 11.2 days. Pre-operatively, maximum creatinine levels (ng/dl) achieved had a median value of 0.7 (IQR: 0.5–1.5). Post-operatively, the mean urine output (mL/kg/h) at 4-h was 4.2 ± 3.7, and at 24-h was 4.5 ± 2.2. Logistic regression analyses showed that those with a post-operative 24-h UOP > 3.5 ml/kg/h had more than 5 times the odds of a prolonged hospital length of stay (LOS) > 3 days (OR: 5.50; 95% CI: 1.23–24.51).DiscussionNeonates with PUV who undergo valve ablation are at risk of POD. Our findings suggest greater urine output after ablation to be a predictor of increased hospital length of stay. Utilizing a urine output (UOP) of >3.5 mL/kg/h may serve as a starting point for defining POD after posterior urethral valve ablation.